ATHENA X-IFU 300 K–50 mK cryochain test results. (December 2020) - Prouvé, T.; Duval, J.M.; Charles, I.; Yamasaki, N.Y.; Mitsuda, K.; Nakagawa, T.; Shinozaki, K.; Tokoku, C.; Yamamoto, R.; Minami, Y.; Le Du, M.; Andre, J.; et al.
Highlight: Cryogenic coupled test of space coolers from 300 K down to 50 mK. Joule Thomson cooler operation with variable heat loads. Hybrid cooler recycling with cooling power provided by space JT coolers. Test of a space cryochain into a GSE cryostat. Abstract: In the framework of the ESA X-ray mission ATHENA, scheduled for launch in 2030, an ESA Core Technology Program (CTP) was started in 2016 to build a flight like cryostat demonstrator in parallel with the phase A studies of the ATHENA/X-IFU instrument. As part of this CTP, called the Detector Cooling System (DCS), design, manufacturing and test of a cryostat including existing space coolers will be done. In addition to the validation of thermal performance, a Focal Plan Assembly (FPA) demonstrator using Transition Edge Sensors (TES) detector technology will be also integrated and its performance characterized versus the environment provided by the cryostat. This is a unique opportunity to validate many crucial issues of the cryogenic part of such a sensitive instrument. A dedicated activity within this CTP-DCS is the demonstration of the 300 K–50 mK cooling chain in a Ground System Equipment (GSE) cryostat. The studies are focused on the operation of the space coolers, which is made possible by the use of a ground cooler for cooling cryogenic shields and mechanical supports. This test program is also the opportunity to validate the operation of the cryochain with respect to various requirements, such as time constant and temperature stabilities. This would bring us valuable inputs to integrate the cryochain in DCS cryostat, X-IFU studies, SPICA and LiteBIRD missions. This paper is focused on the operation of the full 300 K–50 mK cryochain. In particular, the recycling options of the sub Kelvin cooler (sorption cooler + an ADR) versus the capability of 4 K and 2 K JT coolers are described. Results on the JT parameters validation campaign are summarized and eventually the results of the coupled test with sub Kelvin cooler will be presented and discussed.